Bridging the “last mile”: Delivering climate services for agriculture to senior lead farmers in four districts of Zambia. - Gamoyo, Majambo; Koech, Grace; Mwale, Emely; Kiogora, Joseline; Chilambe, Pedro; Ghosh, Aniruddha (2024)
The Alliance of Bioversity International and CIAT worked with partners to train 120 lead farmers in Zambia's Chipata, Chipangali, Kasenengwa and Petauke districts in October 2024. This E-PICSA training equips farmers with climate information to enhance resilience in the 2024/2025 farming season.